'Cultures aren't costumes'. (2nd November 2022) - Unknown
Abstract : This month we share a post from Emi Ito (@little_kotos_words on Instagram), who re-shared her 'cultures aren't costumes' checklist she has created to support people when they are picking Halloween outfits for their children, which will also spark thinking for other celebration days.